2022
DOI: 10.1097/mao.0000000000003629
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Disease-Specific, Generic, and Hearing-Specific Instruments Assessing Health-Related Quality of Life in Patients Undergoing Middle Ear Surgery for Chronic Otitis Media: A Prospective Correlational Study

Abstract: Objective: This study aimed to determine the responsiveness of three instruments (disease-specific, generic, and hearing-specific) assessing health-related quality of life (HRQoL) in adult patients undergoing surgery for chronic otitis media (COM). Study Design: Prospective correlational study. Setting: Two otology referral centers in England, United Kingdom. Patients: Consecutive adult patients undergoing middle ear surgery for COM. Main Outcome Measure(s): HRQoL assessment and audiometry were performed preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…All the studies reported a statistically significant improvement in disease-specific HRQoL scores after otologic surgery among COM w/wo cholesteatoma patients. General HRQoL questionnaires did not detect an impact of surgery among COM patients w/wo cholesteatoma on the HRQoL (8,31,42,43). The significance of improvement in disease-specific HRQoL was independent of the follow-up period.…”
Section: Results Of Individual Studiesmentioning
confidence: 77%
See 4 more Smart Citations
“…All the studies reported a statistically significant improvement in disease-specific HRQoL scores after otologic surgery among COM w/wo cholesteatoma patients. General HRQoL questionnaires did not detect an impact of surgery among COM patients w/wo cholesteatoma on the HRQoL (8,31,42,43). The significance of improvement in disease-specific HRQoL was independent of the follow-up period.…”
Section: Results Of Individual Studiesmentioning
confidence: 77%
“…Additionally, the initial search yielded one eligible study that could not be retrieved with the updated search (43). Together, this resulted in 16 unique fulltext articles (3,8,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) for inclusion in the systematic review (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations